La radiothérapie du cancer de l'endomètre: expérience de l'institut national d'oncologie à propos de 52 cas - Mezouri, Imane (Pan Afr Med J, 2016)
Endometrial cancer is the most common gynecological cancer in the Western world. It affects mainly postmenopausal women. The aim of our study is to report the experience of the radiotherapy department of the National Oncology Institute (INO) in the treatment of endometrial cancer. We retrospectively analyzed 52 cases of endometrial cancer treated in the INO radiotherapy department between 2007-2009. Data obtained from the patient medical records were related to the epidemiologic, clinical, therapeutic and evolutionary aspects of this cancer. The median age of the patients was 57 years, 87% were postmenopausal. The median of consultation time was six months. The main symptom was metrorrhagia (51 patients). Histological diagnosis was based on biopsic curettage of uterine endometrium in 51% of the cases. Anatomo-pathological examination showed an endometrioid adenocarcinoma in 92% of the cases. After the assessment, 27% of the patients were stage I, 30% stage II, 20% stage III and 1% stage IVA, according to the International Federation of Gynecological and Obstetrics (FIGO) stage classification. After surgery, 51% of the patients received postoperative external radiotherapy. The delivered dose was 46 Gray (Gy). All patients received internal vaginal brachytherapy. From an evolutionary perspective, 83% of the patients had no recurrences during the follow-up period, 8% of patients had a local recurrence and 4% of patients had distant metastases. Therefore, surgery is the main treatment for endometrial cancer. Radiotherapy is the primary adjuvant treatment.